Birth Weight and Growth Rate of Bali Cattle Calf - Gemuh, Ayu (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
Research on birth weight and calf growth rate of Bali cattle was carried out in Abian Village, Semarang, Badung, to know the birth weight, body weight gain, and the average calf bodyweight for Bali cattle aged 0-8 months. Using the observational method of Balinese cattle calves from birth to 8 months of age consisting of male and female calves taken randomly. Cows that give birth to calves are weighed and monitored continuously for up to 8 months, monitored and weighed once a month for 8 months. The number of cows observed was 40 calves each, 20 female calves, and 20 male calves. The results showed that the birth weight of Balinese calves varied, both in male and female calves. The birth weight of female calves is 14.50 kg and male calves 16.40 kg, there is a tendency that male calves birth weight is greater than the birth weight of female calves. The calf growth rate of female Bali cows was 0.29 kg/day while males 0.30 kg/day did not have a significant difference between different sexes. The average increase in body weight of male and female calves at the age of 7 months decreased due to weaning. It can be concluded that calf birth weight of Bali cattle is 15.45 + 0.99 kg, where the birth weight of male Bali cattle calves is always heavier than calf calves in Bali cattle. The calf weight gain of Bali cattle varies with the highest body weight gain at 7 months of age.